Specific Aspects of Modelling Heat and Mass Transfer During Condensed Phase Precipitation on Heat Exchanger Walls - Illia Petukhov; Oleksii Lysytsia; Taras Mykhailenko; Artem Kovalov (Engineering Proceedings, 2025)
When the vapour–gas mixture flow heats the cold walls of a heat exchanger, condensed phase (solid and liquid) precipitation can occur on their surfaces. This study aims to improve a model of thermohydraulic processes in a heat exchanger during condensed phase precipitation on its cold surfaces. The process is considered to occur when a multi-component solid-phase layer and a liquid film are simultaneously formed on the wall. Heat is transferred to the interface surface through radiation and convection and due to the phase transition of diffusing components. The mass flow to the interphase surface is determined for each diffusing component. The developed model allows for the calculation of heat transfer parameters in both steady-state and transient conditions, taking into account the formation of a multi-component condensed phase on cold walls.